Co-treatment of gonadotropin and letrozole in infertile women with endometriosis: A double-blind randomized clinical trial - Mahbod Ebrahimi; Firoozeh Akbari Asbagh; Fatemeh Davari Tanha; Hamideh Pakniat; Elham Feizabad; Yasin Rasouli (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: The common causes of infertility in women with endometriosis are folliculogenesis alternation, steroidogenesis and fertilization impairment, oocyte and embryo quality reduction, and implantation defect. Objective: To compare in vitro fertilization (IVF) cycle success rates of women with endometriosis who were treated with letrozole + gonadotropin (LA) vs. placebo + gonadotropin (PA). Materials and Methods: This double-blind, randomized clinical trial study was conducted with 94 infertile women with endometriosis (47 in the LA group and 47 in the PA group) who were candidates for IVF, from April-June 2021. For all participants, the long agonist protocol was applied. In both groups, gonadotropin-releasing hormone agonist was prescribed in the mid-luteal stage and from the third day of the cycle, and gonadotropin was started and its doses were regulated based on the patient's age, serum anti-Mullerian hormone and follicle-stimulating hormone. From the third day of the menstrual cycle, 5 mg of letrozole daily for 5 days was prescribed for the LA group, while the placebo was prescribed for the PA group on the identical days and duration. After embryo transfer, biochemical and clinical pregnancy were measured in the 2 groups. Results: The gonadotropin dosage (p < 0.01) and estradiol level (p = 0.02) on the human chorionic gonadotropin administration day were significantly lower in the LA group compared with in the PA group. Fetus transfer was done for 32 women. No significant differences were detected between the study groups regarding biochemical or clinical pregnancy (p = 0.72 for both). Conclusion: Letrozole as a co-treatment drug in the IVF cycle of women with endometriosis can significantly reduce the gonadotropin dosage and estradiol level with the same pregnancy rates.